2020
DOI: 10.1093/nar/gkaa1064
|View full text |Cite
|
Sign up to set email alerts
|

CSEA-DB: an omnibus for human complex trait and cell type associations

Abstract: During the past decade, genome-wide association studies (GWAS) have identified many genetic variants with susceptibility to several thousands of complex diseases or traits. The genetic regulation of gene expression is highly tissue-specific and cell type-specific. Recently, single-cell technology has paved the way to dissect cellular heterogeneity in human tissues. Here, we present a reference database for GWAS trait-associated cell type-specificity, named Cell type-Specific Enrichment Analysis DataBase (CSEA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…According to our tissue cell-type-specific expression database (CSEA-DB), CXCR6 is mainly expressed in immune cells in human lung tissue (e.g., T cell and NK cell) [16]. In Liao et al’s work, the authors reported that CXCR6 had lower expression in severe patients than moderate patients, indicating a potential protective effect in T cells of human respiratory systems [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our tissue cell-type-specific expression database (CSEA-DB), CXCR6 is mainly expressed in immune cells in human lung tissue (e.g., T cell and NK cell) [16]. In Liao et al’s work, the authors reported that CXCR6 had lower expression in severe patients than moderate patients, indicating a potential protective effect in T cells of human respiratory systems [17].…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in single cell transcriptome sequencing provide unprecedented opportunities to understand the biological mechanism underlying disease pathogenesis at the single cell and cell type levels [14][15][16]. The recent generation of single cell RNA-sequencing (scRNA-seq) data from the bronchoalveolar lavage fluid (BALF) of moderate and severe COVID-19 patients has revealed the landscape of the gene expression changes in major immune cells.…”
mentioning
confidence: 99%
“…In recent years, large consortia like GTEx (Genotype-Tissue Expression), eQTLGen Consortium, and DICE (database of immune cell expression) have generated rich eQTLs resources in diverse tissues and immune-related cell types (GTEx Consortium 2020 ; Schmiedel et al 2018 ; Võsa et al 2018a ). A variety of statistical approaches, such as transcriptome-wide association study (TWAS) analysis and colocalization analysis, have successfully interpreted the target genes of non-coding variants by integrating the context-specific eQTLs (Dai et al 2020 ; Dai et al 2019 ; Gamazon et al 2015; Giambartolomei et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We applied deCS algorithm to the GWAS data in our recently developed database, Cell type-Specific Enrichment Analysis DataBase (CSEA-DB), which covers 55 unique tissues [69]. Among a total of 10,250,480 trait-cell type associations, we observed significant cell type association in 598 (11.68%) traits.…”
Section: Discussionmentioning
confidence: 99%